Detection of two potent synthetic opioids carfentanil and 3-methylfentanyl in forensic investigations during a four-year period 2017‒2020. (2021) - Noble, Carolina; Papsun, Donna M.; Diaz, Stephanie; Logan, Barry K.
Abstract: There has been an alarming increase of novel synthetic opioids (NSOs) in the illegal drug market since 2016. These substances are still detected in forensic case investigations in biological samples as well as in seized materials. Although NSOs are steadily emerging, other potent "old" synthetic opioids are still circulating and involved in fatal overdose cases. This is the case of the potent designer drugs carfentanil and 3-methylfentanyl. These drugs were associated with several deaths since at least 20 years ago, and they are still a public health threat. In this study, we presented postmortem (PM) forensic cases that were positive for carfentanil or 3-methylfentanyl over a four-year period 2017–2020. Quantitative confirmation was via a quantitative liquid chromatography tandem mass spectrometry (LC-MS/MS)-based method that targets 21 designer opioids, able to differentiate isomers such as cis- and trans-3-methylfentanyl, with a limit of quantification of 0.05 ng/mL. A total of 1136 and 153 PM cases were received in the laboratory from different regions of the United States positive for carfentanil and 3-methylfentanyl, respectively. PM peripheral blood ranged from 0.050‒32 ng/mL for carfentanil,  and 0.057‒7.2 and 0.057‒2.2 ng/mL for cis- and trans-3-methylfentanil, respectively. During this period, fentanyl was the most common concomitant drug detected within these cases. Heroin and cocaine were also highly prevalent in those cases positive for carfentanil. Other NSOs such as 2-furanylfentanyl, cyclopropylfentanyl and para-fluorobutyrylfentanyl were also significant findings in positive carfentanil cases. For 3-methylfentanyl, cocaine was the second most prevalent co-occurrence drug, while heroin decreased over the years in those cases where 3-methylfentanyl was confirmed.